Platelet-Poor Plasma as a Supplement for Fibroblasts Cultured in Platelet-Rich Fibrin - Luiz Alexandre Chisini; Sarah Arangurem Karam; Thaís Gioda Noronha; Letícia Regina Morello Sartori; Alissa Schmidt San Martin; Flávio Fernando Demarco; Marcus Cristian Muniz Conde (University of Zagreb. School of Dental Medicine, 2017)
The aim of this study was to evaluate the proliferation and adhesion of mesenchymal cells (3T3/NIH) in Dulbecco's Modified Eagle Medium (DMEM) supplemented with Platelet-Poor Plasma (PPP) in a Platelet-Rich Fibrin (PRF) scaffold. Human blood was obtained and processed in a centrifuge considering the equation G=1.12xRx (RPM/1000)² to obtain PRF and PPP. Cell adhesion and maintenance analyses were performed by MTT assays in a 96 well plate with supplemented DMEM: PPP (90:10) for 24 hours. Besides, the PRF was deposited in a 48 well plate and 10x104 cells were seeded above each PRF (n=3) with 800μl of DMEM: PPP (90:10) and cultured for 7 days. Histological analysis and the immunohistochemical staining for Vimentin were performed. Results were analyzed by one-way ANOVA in Stata12®. A significant decrease (p<0.05) of cells adhesion in relationship to FBS was observed. However, a similar ability of cell-maintenance for PPP 10% was observed (P>0.05). Fibroblasts culture for 7 days in PRF supplemented with PPP 10% was possible, showing positive staining for Vimentin. Therefore, PPP cell supplementation decreased the initial adhesion of cells but was able to maintain the proliferation of adhered cells and able to support their viability in PRF. It seems that this method has many clinical advantages since it provides an autologous and natural scaffold with their respective supplement for cell culture by only one process, without using xenogeneic compounds. This could improve the potential of clinical translational therapies based on the use of PRF cultured cells, promoting the regenerative potential for future use in medicine and dentistry.